2015
DOI: 10.6090/jarq.49.23
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Compensatory Growth with Changing Levels of Dietary Lysine from Deficient to Sufficient in Pigs

Abstract: This review describes our studies on compensatory growth, specifically the growth that occurs after dietary lysine deficiency is changed to sufficiency. We found that dietary lysine sufficiency induced compensatory growth in pigs after dietary lysine deficiency. We also showed that compensatory growth of pigs induced by dietary lysine sufficiency was partly attributed to greater N retention. In a rat model, both suppression of proteolysis and increased protein synthesis in skeletal muscle contributed to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Tokach et al [ 18 ] also reported that different levels of milk by-product (0% or 40%) in weaning pig diets produced significant differences in growth performance only during the weaning period and any significant difference was not observed in growth performance during the growing-finishing. Also, growth retardation due to nutrient limitation in weaning pigs induced compensated growth of growing-finishing pigs resulting in similar BW at the end of finishing period [ 19 , 20 ]. Weaning pigs with low growth rate due to limited nutrient intake recovered the normal growth rate compared with other pigs on the same nutritional supply [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tokach et al [ 18 ] also reported that different levels of milk by-product (0% or 40%) in weaning pig diets produced significant differences in growth performance only during the weaning period and any significant difference was not observed in growth performance during the growing-finishing. Also, growth retardation due to nutrient limitation in weaning pigs induced compensated growth of growing-finishing pigs resulting in similar BW at the end of finishing period [ 19 , 20 ]. Weaning pigs with low growth rate due to limited nutrient intake recovered the normal growth rate compared with other pigs on the same nutritional supply [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Weaning pigs with low growth rate due to limited nutrient intake recovered the normal growth rate compared with other pigs on the same nutritional supply [ 21 ]. Ishida et al [ 20 ] reported that compensatory growth of pigs induced by lysine sufficiency was partly attributed to greater N retention which increased protein synthesis in skeletal muscle. In this way, pigs fed low milk by-product diet had growth retardation compared with pigs fed high milk by-product diet, however, compensated growth occurred in growing-finishing period.…”
Section: Resultsmentioning
confidence: 99%